PENERAPAN METODE USER CENTERED DESIGN PADA PENGEMBANGAN ANTARMUKA APLIKASI KESEHATAN HEWAN - Ifandi, Ahmad Azrul; Kusumandyoko, Tri Cahyo (Universitas Negeri Surabaya, 2023)
The significant growth in the number of emerging diseases originating from animals highlights the importance of adopting a holistic approach to animal health as a means to address and prevent the spread of various diseases. This research aims to develop an animal health app using a user centered design (UCD) method by Garet (2010). The development methodology involves qualitative and the analysis using the Miles & Huberman method, focusing on identifying and resolving issues that arise in each user scenario. User feedback is incorporated through prototype testing, enabling better improvements and refinements. The UCD method ensures that the application development is centered around user needs and preferences. The development process includes data analysis from various sources, designing solutions encompassing feature details and user journey maps, and creating prototypes for user testing. The results of the development of the prototype of the animal health application demonstrate that, overall, this development provides users with a significantly improved user experience compared to the previous version. Additionally, it effectively meets the users' needs.